A meta-ethnography of patients' experiences of chronic pelvic pain: struggling to construct chronic pelvic pain as 'real'. - Toye, F; Seers, K; Barker, K (2014)
AIM: To review systematically and integrate the findings of qualitative research to increase our understanding of patients' experiences of chronic pelvic pain. BACKGROUND: Chronic pelvic pain is a prevalent pain condition with a high disease burden for men and women. Its multifactorial nature makes it challenging for clinicians and patients. DESIGN: Synthesis of qualitative research using meta-ethnography. DATA SOURCES: Five electronic bibliographic databases from inception until March 2014 supplemented by citation tracking. Of 488 papers retrieved, 32 met the review aim. REVIEW METHODS: Central to meta-ethnography is identifying 'concepts' and developing a conceptual model through constant comparison. Concepts are the primary data of meta-ethnography. Two team members read each paper to identify and collaboratively describe the concepts. We next compared concepts across studies and organized them into categories with shared meaning. Finally, we developed a conceptual model, or line of argument, to explain the conceptual categories. RESULTS: Our findings incorporate the following categories into a conceptual model: relentless and overwhelming pain; threat to self; unpredictability, struggle to construct pain as normal or pathological; a culture of secrecy; validation by diagnosis; ambiguous experience of health care; elevation of experiential knowledge and embodiment of knowledge through a community. CONCLUSION: The innovation of our model is to demonstrate, for the first time, the central struggle to construct 'pathological' vs. 'normal' chronic pelvic pain, a struggle that is exacerbated by a culture of secrecy. More research is needed to explore men's experience and to compare this with women's experience.